Comparative Study between Quartz Laser Ablation of Prostate (QLAP) and Transurethral Resection of Prostate (TURP) - Shaker, Hassan S; Saafan, Ahmed; Khedr, Ashraf; Attia, Hatem Soltan (QJM : An International Journal of Medicine, 2024)
Background & Purpose Pulsed beams produced by laser at wavelength of 2140nm which have above 60% absorption by water that result in vapor bubble which has a destructive effect on tissues and atones (jack hummer effect) but with limited coagulation make it suitable for small sized prostate below 60gm and/or bladder neck incision--. This study was conducted to compare the safety and efficacy of transurethral resection of prostate (TURP) versus Quartz Laser Ablation of prostate (QLAP) regarding patient outcome and intraoperative complications. Study Design Prospective, case controlled comparative study. Setting Ain Shams, Shaker and Maadi military hospitals. Subjects We included 100 patients with lower urinary tract symptoms (LUTS) symptoms secondary to benign prostate enlargement (BPE), and classified them two groups: 50 patients treated by monopolar Transurethral Resection of Prostate (TURP) (Group A), and 50 patients treated by Quartz Laser Ablation of Prostate (QLAP) (Group B). Methods All patients were subjected to full history taking, examination, Preoperative laboratory investigations including, Hemoglobin, hematocrit, serum Na and K and serum PSA. Perioperative radiological investigations including, abdominopelvic ultrasound with pre and post void residual urine, transrectal ultrasound to estimate the prostate size and uroflowmetry. Follow up 6 months post operative for any complication, change in IPSS score, serum PSA, urine analysis, post voiding residual and uroflowmetry were evaluated. Results In the studied population, the average age was (68.03 ± 8.2) years. Comparative study between two groups revealed non- significant difference among post-operative urological data. However, there is a significant difference in median value of PVR but not in median difference value. Similarly, there is no statistically significant difference as regard to laboratory findings with an exception to potassium level. Regarding post-operative complications; the early complications rate was (28%), and the late complications rate was (25%). Comparative study between the 2 groups revealed non-significant difference as regards post-operative complications (p > 0.05). Conclusion To conclude, QLAP technique for management of BPH was proven to be effective in decreasing post-operative PSA, prostate size, IPSS total, and PVR. But, both QLAP and Monopolar TURP techniques had the comparable safety and complications rates.